Global dynamics for two-species competition in patchy environment - Kuang-Hui Lin; Yuan Lou; Chih-Wen Shih; Tze-Hung Tsai (Mathematical Biosciences and Engineering)
An ODE system modeling the competition between two species in a two-patch environment is studied.Both species move between the patches with the same dispersal rate. It is shown that the species with largerbirth rates in both patches drives the other species to extinction, regardless of the dispersal rate. The more interesting case is when both species have the same average birth rate but each species has larger birth rate in one patch. It has previously been conjectured by Gourley and Kuang that the species that can concentrate its birth in a single patch wins if the diffusion rate is large enough, and two species will coexist if the diffusion rate is small. We solve these two conjectures by applying the monotone dynamics theory, incorporated with a complete characterization of the positive equilibrium and a thorough analysis on the stability of the semi-trivial equilibria with respect to the dispersal rate. Our result on the winning strategy for sufficiently large dispersal rate might explain the group breeding behavior that is observed in some animals under certain ecological conditions.